The possible techniques that used to improve the bioavailablity, pharmacological activity, solubility and permeability of anti-viral drugs: Insight for COVID-19 antiviral drugs - Ghassan Mudher Hashim; Ghaidaa S. Hameed; Dalya Basil Hanna (College of Pharmacy / Mustansiriyah University, 2023)
In early March of 2020, the world was hit by a pandemic caused by the new SARS-COV-2 coronavirus dubbed by the WHO (World health organization) as COVID-19. More than two years later and a series of lockdowns worldwide as a measure to combat the viral spread, had the world facing detrimental effects on health, economic and social fronts. The principal weapon in the worldwide fight against viruses such as corona virus illness in 2019 (COVID-19) is antiviral medicines (AvDs). Because of their low oral bioavailability and limited effectiveness owing to their low solubility/permeability, most AvDs need numerous doses, and their usage commonly results in drug resistance. Solving the issues with AvDs and improving their effectiveness might be aided by a better understanding of their in vivo metabolic and pharmacokinetic properties. In this review the AvDs, were systematically investigated regarding their cellular pharmacology, pharmacokinetics and pharmacodynamics. Additionally, delivery systems used for AvDs to achieve better pharmacology were reviewed. This review assumed that using sophisticated nanotechnology and the right administration routes, together with proper solid dispersion technology and nanosystems, may assist to obtain superior pharmacological activity and pharmacokinetic behavior of AvDs. Antiviral drugs (AvDs) that have been shown to bind to the SARS-CoV-2 receptor are promising candidates for treating COVID-19. These include ribavirin, remdesivir, favipiravir (FAV), chloroquine, lopinavir, and ritonavir.